Effect of SHP2 on proliferation and B-cell receptor signaling in a chronic lymphocytic leukemia cell model - Sarah Naomi Bolz (2019)
In chronic lymphocytic leukemia (CLL) B-cell receptor (BCR) signaling plays a crucial role for the survival and proliferation of the malignant cells. This molecular system is greatly built up of kinases and phosphatases that use sarcoma (SRC)-homology 2 (SH2) domains to pursue their functions. An SH2-domain screening of 34 CLL patients was performed to find critical participants in pathologic BCR signaling and revealed a correlation between a long time to first treatment and a high binding activity of SH2-domain containing tyrosine phosphatase 2 (SHP2). To identify cellular mechanisms by which SHP2 binding influences BCR signaling in CLL, SHP2 wild type and a phosphatase inactive mutant were overexpressed in the CLL cell line MEC1. Additionally, a SHP2 directed knockdown in MEC1 was generated by small hairpin RNA (shRNA). Overexpression of SHP2 wild type, but not the phosphatase disabled mutant, negatively influenced proliferation and induced anergic characteristics in MEC1: Basal Ca2+ and mitogen activated protein kinase signaling were enhanced, while surface immunoglobulin M levels and BCR responsiveness were downregulated. Moreover, ibrutinib synergized with SHP2 overexpression in anti-proliferative effects. Together with the results of SH2-domain screening, these data suggest that SHP2 promotes the cellular state of anergy and thus an indolent clinical course in CLL. Notably, the results identify SHP2 as the previously unknown molecular link between the major anergic hallmarks.